Perangkat Lunak Bantu Penerimaan Siswa Baru Pada SD Methodist-5 Pagar Alam - Desi Puspita (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2017)
Software is a computer program associated with software documentation such as need documentation, design model, and user manual or a computer program without associated documentation. Software built by engineering is not manufactured by manufacture or manufacturer. The purpose of the development of software aids is to assist data collection in the process of admission of new students in SD Methodist-5 Pagar Alam. The process of data collection applied in SD Methodist-5 Pagar Alam is by using conventional method, that is by recording data process of new student acceptance which still using ledger, so that in process of data searching and report making can take a long time. Software development model used in this research is waterfall model that includes: System Engineering, Requirement analysis, Design, Coding, Testing and Maintenance.